Crime and Deviance : An Introduction to Criminology - Tibamanya mwene Mushanga (Book collections on Project MUSE., 2011)
The main objective of the first edition was to make available a simplified, readily available introductory reader not only for the students of criminology, but also for the general reader who may be interested in the problems of crime, crime control and prevention.